Protocol for a Randomized Controlled Trial of CI Therapy for Rehabilitation of Upper Extremity Motor Deficit: The Bringing Rehabilitation to American Veterans Everywhere Project. Issue 4 (July 2019) - Morris, David M.; Taub, Edward; Mark, Victor W.; Liu, Wei; Brenner, Lisa; Pickett, Treven; Stearns-Yoder, Kelly; Bishop-McKay, Staci; Taylor, Andrea; Reder, Laura; Adams, Terrie; Rimmer, James; et al.
Abstract : Constraint-induced movement therapy (CI therapy) has been shown to reduce disability for individuals with upper extremity (UE) hemiparesis following different neurologic injuries. This article describes the study design and methodological considerations of the Bringing Rehabilitation to American Veterans Everywhere (BRAVE) Project, a randomized controlled trial of CI therapy to improve the motor deficit of participants with chronic and subacute traumatic brain injury. Our CI therapy protocol comprises 4 major components: (1) intensive training of the more-affected UE for target of 3 hour/day for 10 consecutive weekdays, (2) a behavioral technique termed shaping during training, (3) a "transfer package, " 0.5 hour/day, of behavioral techniques to transfer therapeutic gains from the treatment setting to the life situation, and (4) prolonged restraint of use of the UE not being trained. The primary endpoint is posttreatment change on the Motor Activity Log, which assesses the use of the more-affected arm outside the laboratory in everyday life situations. Data from a number of secondary outcome measures are also being collected and can be categorized as physical, genomic, biologic, fitness, cognitive/behavioral, quality of life, and neuroimaging measures.